Aplikasi Perhitungan Biaya Pembuatan Bangunan Rumah Tinggal Pada CV. SANCITA - Aji Permana; Heri Herwanto (Universitas Kuningan, 2022)
Indonesia is a developing country with a large number of its Population and its fast growth each year. Therefore the needs of Houses and other public facility will simultaneously increase and become the most important needs. In addition, there are still a lot of Indonesian people that still can afford a decent place to live.The calculation of the budget plan (RAB) is needed both for its own architects and consumers who will build a place to live. With so architects can estimate the required budget plan in accordance with the type of House desired by consumers. Often in the execution of a job became inefficient, both in the use of labor and raw materials due to lack of preparation of the draft budget calculations of cost to make the dwelling. Thus we need to plan and determine the budget very carefully, to avoid wasteful expense, or even lack of funds. Key Words : The calculation of the budget plan (RAB)